PENGARUH KEYAKINAN DIRI (SELF EFFICACY) TERHADAP KOMUNIKASI INTERPERSONAL MAHASISWA TAHUN PERTAMA - Angraini, Dila; Ninil Elfira; Fitriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of self-efficacy on interpersonal communication among first-year students of the Guidance and Counseling Study Program at Universitas Jambi. This research employed a quantitative approach using an ex post facto method. The population consisted of 109 first-year students, with a sample of 86 students selected through simple random sampling. Data were collected using Likert-scale questionnaires that had been tested for validity and reliability. The self-efficacy instrument consisted of 17 items with a reliability coefficient of 0.737, while the interpersonal communication instrument consisted of 25 items with a reliability coefficient of 0.732. Data analysis techniques included descriptive analysis, normality test, linearity test, and simple regression analysis. The results showed that the level of students’ self-efficacy was in the high category (81.04%), while interpersonal communication was in the moderate category (67.15%). The simple regression analysis indicated a significance value of 0.001 (p < 0.05), which means that self-efficacy has a significant effect on interpersonal communication among first-year students.